The cytotoxic activity of Ziziphus Jujube on cervical cancer cells: In Vitro study - Hoshyar, R; Jamali, S; Fereidouni, M; Abedini, M R (Cellular and Molecular Biology, 2015)
Recently, there are tendency to use natural products such as Ziziphus Jujube (Jujube) as therapeutic agents for cancer. Understanding the molecular mechanisms of anti-cancer effects of Jujube may improve the current therapeutic strategies against cervical cancer. Our MTT data showed a significant dose- and time-dependent inhibition of OV-2008 cell proliferation following Jujube administration. Moreover, qRT-PCR analyses significantly revealed the suppression of cyclin D1 and the enhancement of P53, P21 and P27 expression in treated cells. These results suggest that the herb exerts a cytotoxic effect on cervical cancer cells through alternation of the expression of the genes that are involved in regulation of cell cycle.